Comparison of Wide Conjunctival Flap and Conjunctival Autografting Techniques in Pterygium Surgery - Lokman Aslan; Murat Aslankurt; Adnan Aksoy; Murat Özdemir; Erdem Yüksel (Journal of Ophthalmology)
Pterygium is an abnormal fibrovascular tissue extending on the cornea which is a degenerative and hyperplastic disorder. A stromal overgrowth of fibroblast and blood vessels is accompanied by an inflammatory cell infiltrate and abnormal extracellular matrix accumulation. The surgical excision is the main treatment method of pterygium, but recurrence is the most common postoperative complication. In the present study, we aimed to compare the wide conjunctival flap and the conjunctival autografting techniques in pterygium surgery according to time of operation, safety, and effectiveness. Results showed that the effect of wide conjunctival flap techniques on primary pterygium surgery was found close to the conjunctival autograft techniques. In addition, the flap technique has a shorter surgical time, the surgery does not require extreme experience, feeding of the flap is provided with own vessels since the vascular structure is protected on the upper temporal conjunctival area, reverse placement of the flap is not seen, it needs fewer sutures, so that suture disturbances may reduce, and it is less traumatic than autograft technique during conjunctival transport. Therefore, this technique may be preferred in suitable cases.